Impact of Capital Market on Domestic Resource Mobilization for Economic Development in Nigeria (2000-2015) (2016)
The study investigated the impact of Nigerian capital market on domestic resource mobilization for economic development, using time series data from 2000 to 2015. The study employed secondary data obtained from the Central Bank of Nigeria Statistical Bulletin, the Nigerian Stock Exchange Fact Book and Securities and Exchange Commission database. To evaluate the impact of the independent variables on the dependent, the ordinary least square (OLS) method of estimation was employed. Augmented Dickey Fuller (ADF) test was used to identify the order of integration. Economic growth was proxied by Gross Domestic Product (GDP) while the capital market variables considered include: Market Capitalization (MCAP), Total New Issues (TNI) and value of transactions (VLT). Applying Johansen and Juselius co-integration test, the result showed that there was at most one co-integrating equation in the model, implying that there is a long run relationship between the variables in the model. The causality test results suggest bidirectional causation between the GDP and the value of transactions (VLT) and to the GDP but not vice-versa. Using two-tailed test, the F-statistics is significant at 5 percent level of significance. Furthermore, there was no evidence of reverse causation from GDP to market capitalization and there was no evidence of independence causation between the GDP and total new issues (TNI). The study showed that the major problem with domestic resource mobilization in Nigeria have been that not enough savings are being generated to facilitate the required investment. Also, the type of savings available does not easily make financial intermediation possible. The Nigerian stock market has been constrained by policies that tend to make the exchange look like a mechanism by which government raise loan finance rather than an instrument for mobilizing industrial finance. It is recommended therefore that the regulatory authority should appraise and modify the restrictive policies that constrained resource mobilization capacity of the Nigerian capital market